Treme. The complete fourth season [videorecording (DVD)] - Simon, David, 1960-; Overmyer, Eric (Home Box Office, Inc., 2014)
New Orleans, 38 months after. The city's musicians, chefs, Mardi Gras Indians, and others continue to rebuild their lives in the aftermath of Hurricane Katrina. But the promise of recovery, heightened by the historic election of a new president, is tempered by sobering economics, continued police corruption, and the ongoing specter of violence and crime. In these five final episodes of Treme, New Orleans' protagonists strive to build their own legacy in this most iconic of American cities.